2015
DOI: 10.1364/ao.54.000204
|View full text |Cite
|
Sign up to set email alerts
|

Measurement method for optical retardation based on the phase difference effect of laser feedback fringes

Abstract: We present a measurement method for optical phase retardation, which utilizes a phase-difference phenomenon of the feedback fringes in orthogonally polarized directions of a laser with anisotropic weak feedback. This phase difference is dominated by the measured retardation. The measurement principles are given based on the 3-mirror cavity model, and experiments are conducted with quartz waveplates (WPs). A measurement range 0°-180° is achieved, the uncertainty is theoretically better than 0.5°, and the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…By adding a birefringence component into the laser feedback cavity, the polarization states of the feedback light can be shifted and the laser output intensities in the two orthogonal directions with the phase difference can be modulated. [31][32][33][34] The birefringence components are usually in the form of wave plates or quartz crystals. When the birefringence component is put into the external cavity, the original external cavity forms two different physical external cavities.…”
Section: Polarization-shifted Feedbackmentioning
confidence: 99%
“…By adding a birefringence component into the laser feedback cavity, the polarization states of the feedback light can be shifted and the laser output intensities in the two orthogonal directions with the phase difference can be modulated. [31][32][33][34] The birefringence components are usually in the form of wave plates or quartz crystals. When the birefringence component is put into the external cavity, the original external cavity forms two different physical external cavities.…”
Section: Polarization-shifted Feedbackmentioning
confidence: 99%
“…In Nd:YAG lasers, the phase difference between orthogonal polarization components signal of optical feedback can be observed, which is about twice as large as the phase retardation of the birefringent element [15]. Further research has shown that the feedback laser component perpendicular to the initial polarized laser oscillate, and this effect is accompanied by a slight change in the polarization state of the laser [16][17][18]. However, in lasers with an anisotropic medium,these phenomena-primarily polarization flipping and phase difference of LBF have only sometimes been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied some other methods such as laser feedback [14], laser frequency splitting [15], and Mueller matrix ellipsometry [16,17]. The laser feedback method measures the phase retardation by inserting the MWP between the laser and a feedback mirror to gain a polarization jump, and analyzing the relationship between the measurement signals' phase difference and MWP's phase retardation at resonance state.…”
Section: Introductionmentioning
confidence: 99%